Impact of variable photospheric radius on exoplanet atmospheric retrievals. Issue 1 (22nd March 2022) - Taylor, Jake
ABSTRACT: Inverse techniques are used to extract information about an exoplanet's atmosphere. These techniques are prone to biased results if the appropriate forward model is not used. One assumption used in a forward model is to assume that the radius of the planet is constant with wavelength; however, a more realistic assumption is that the photospheric radius varies with each wavelength. We explore the bias induced when attempting to extract the molecular abundance from an emission spectrum, which was generated with a variable radius. We find that for low-gravity planets, the retrieval model is not able to fit the data if a constant radius model is used. We find that biased results are obtained when studying a typical hot Jupiter in the MIRI LRS wavelength range. Finally, we show that high-gravity planets do not suffer a bias. We recommend that future spectral retrievals that interpret exoplanet emission spectra should take into account a variable radius.